2016
DOI: 10.1053/j.semnuclmed.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Nuclear Medicine Practice in the Middle East

Abstract: The practice of nuclear medicine (NM) in the Middle East region has experienced an important growth in the last 2 decades and has become crucial in providing healthcare to the region's population of about 395 million people. Even though there are some countries in which the services provided are limited to basic coverage of studies with (99m)Tc and (131)I, most have well-established practices covering most of the available studies in this medical specialty; this is the case in for example, Iran, Israel, Kuwait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 1 publication
2
23
0
Order By: Relevance
“…The number of centers administering MRT in different countries was reported, identifying a total of 630 centers. In addition to that survey [ 3 ], a few national surveys have been identified [ 4 , 5 ], as well as one reviewing nuclear medicine in the Middle East [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of centers administering MRT in different countries was reported, identifying a total of 630 centers. In addition to that survey [ 3 ], a few national surveys have been identified [ 4 , 5 ], as well as one reviewing nuclear medicine in the Middle East [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Re-DMSA complex, with potential application in radionuclide therapy of medullary thyroid carcinoma and bone metastases in prostate cancer, which also emerged in the 1990s, [4][5][6][7] Tc, most of these agents and methods were established in the 1990s and although clinical applications have begun to take hold (all of which are based on "phase 1" and "phase 2" chemistry described above, as illustrated in other contributions to this issue), little new 188 Re chemistry development has occurred since that time. This unfortunate trend is reflected in the chart shown in Figure 1, Re radionuclide therapies in some countries, [9,10] 188 Re generator availability is improving again and the scene is set for a resurgence of development of both 99m Tc and 188 Re chemistry development, reversing the recent trend (see Figure 1) that has seen the collapse of basic research on the chemistry of these radionuclides since 2000. The most comprehensive review of 188 Re radiopharmaceutical chemistry dates back to 1999 [11] and the reader is referred to that review for a summary of the state-of-the-art pre-2000, as well as to reviews published within the last decade covering bifunctional chelator and bioconjugation development for labelling peptides and proteins with both 99m Tc and 188 Re [12][13][14].…”
Section: The Development Of the Chemistry Of 188mentioning
confidence: 99%
“…When Technetium‐99m HYNIC PSMA is used as the radiopharmaceutical, imaging is done with a gamma camera. There are more gamma cameras installed worldwide than there are PET cameras …”
Section: Introductionmentioning
confidence: 99%
“…There are more gamma cameras installed worldwide than there are PET cameras. 10 The synthesis and biodistribution of Tc-99m HYNIC PSMA in animals and humans have been reported. 11,12 Few studies have reported promising results with the use of Tc-99m-labeled PSMA ligand SPECT/CT imaging in patients with prostate carcinoma.…”
Section: Introductionmentioning
confidence: 99%